Insecticide groups and their effects in aquatic environment - Kayhan, Figen Esin; Kaymak, Güllü; Yön, Nazan Deniz (Marmara Üniversitesi Fen Bilimleri Dergisi, 2013)
Over the past decade aquatic environments have become more contaminated by insecticides. Insecticides have a toxic effect on aquatic organisms and they become a part of the food chain by accumulation. Therefore it is very important to study the effects of subchronic exposure to environmental concentrations of insecticides on aquatic organisms. The aim of this review is to investigate different effects of insecticide groups on aquatic organisms in aquatic environment.
Keywords: Insecticides; Aquatic environment; Ecology